How Do National Governments Affect Higher Education System? An Analysis of the Autonomy of the Public Universities In Mozambique - Collinson, Ivan V (Pensamento & Realidade, 2019)
The present study is an effort to discuss the relationship which has been established during time between Government and Public Institutions of Higher Education in Mozambique (PIHEd). Historically in Mozambique, the political system in force was not always the same (Mário Mário, Fry, Levey, Chilundo, 2003), actually, throughout the history, the political environment was changed from (i) the Portuguese colonial period, (ii) the post-independence period and the adoption of socialism and finally, (iii) with the democratic system, where economy of market was adopted has economic system (Mário et al, 2003). According to Mário et al(2003) and Beverwijk (2003), higher education was not left without these changes and it had reacted accordingly to specific historical and political moment, as a proof of the existence of Path-Dependency Theory, which analyses the preconditions and cultural features and its influence on how institutions develop (Ramirez & Christensen, 2012). During all these periods, public universities, starting with the first, Eduardo Mondlane University, had different types of relationship with the governmental authorities at the time. And the nature of this relationship had exerted a certain degree of influence to the university governance, accordingly to Beverwijk (2003). These influences, when examined in light of managerial theoretical frameworks, more specifically the Agency Theory, are more likely to be conflicting in terms of governance, according to a similar study conducted in Finland (Kivisto, 2007). Although the main objective is not the same, partially, this study intends to discuss the type of relationship which has been established between the Government and PIHEd in Mozambique (namely, Eduardo Mondlane University, Pedagogical University, Lúrio University and University of Zambeze) in order to understand the relationship between government and university, and how likely conflicts can occur at the field of university governance. In resume, the lack of understanding on how public universities were shaped, in terms of university governance, and how the political environment led to the selection of a particular model of governance, conducts this research to a path of discovery, throughout the history of development of public higher education in Mozambique. Key-Words:university governance · university autonomy · models of university governance · agency theory.